Legal technology: A comprehensive analysis of their impact on legal industry and enhancing entrepreneurial opportunities - Ramos, Fernando (Derecho Global. Estudios sobre Derecho y Justicia, 2023)
The continuous development of technology, showed an ongoing discussion about the impact of robots, artificial intelligence, and digitalization on our daily lives and professions. This article aims to analyze the advantages, disadvantages, and regulatory issues related to legal technologies in business. Specifically, it focuses on the use of technological tools in legal work and how lawyers can adapt and acquire the necessary skills. A thorough literature review was conducted to examine the influence of legal technology on commercial legal science. The findings reveal that legal technology plays a vital role in automating tedious tasks, improving efficiency, and reducing human errors within the field. Legal technology is intended to enhance lawyers' work rather than replace them entirely. Overcoming obstacles requires investing in adequate training programs while gradually adopting new behaviors within the industry.